Experimental and Numerical Investigation of the Effect of Temperature on Deep Drawing of Aluminum Alloy - Ozek, Cebeli; Tasdemir, Vedat (Gazi Univ, 2018)
5000 series of Al-Mg alloys have found very wide application areas due to their ductility, good weldability, high strength and low weight properties. However, forming of these alloys is more difficult than steel sheets at room temperature due to their microstructure. The most effective way to overcome these problems is the warm forming. In this study, the effect of forming temperature on limit drawing ratio, punch force, wall thickness, microhardness and stress of cup were investigated experimentally and numerically. The experiments were conducted at 25 degrees C, 100 degrees C, 175 degrees C, and 250 degrees C temperatures under 3600 N blank holder force. As a result of the studies, it was determined that an increase in forming temperature led to more homogeneous distribution of wall thickness, increase of limit drawing ratio, decrease of microhardness, stress and punch forces. The finite element analysis (FEA) model results were also in a good agreement with the experimental results.
Keywords: AA5754 sheet metal; limit drawing ration; warm deep drawing; microhardness; finite element analysis